Om växelverkan mellan straffrätt och straffprocessrätt ur ett finländskt perspektiv - Dan Frände (Nordisk Tidsskrift for Kriminalvidenskab)
Criminal law and procedural law have always been closely related. It is quite clear that these disciplines are highly dependent of each other. Every modern democracy needs a material as well as a formal side. One can, e.g., argue that a weak and undeveloped criminal procedure is a constant threat to the fundamental human rights and freedoms of the citizens. But is there an actual interaction between criminal law and criminal procedure? In my opinion, such an interaction exists. This is noticeable on a concrete level, i.a. in the submission of evidence. Dogmatic research, too, should always cover both fields. Whenever possible, the formation of rational concepts requires a terminology that is familiar to both criminal law and criminal procedure.